Psychophysiological states and motivation in elite judokas - Korobeynikov, G.; Mazmanian, K.; Korobeynikova, L.; Jagiello, W. (Archives of Budo, 2010)
Background and study aim: Examine the effects of different level combination of motivation to achieve success and motivation to avoid failure on psychophysiological states in elite judokas. Material and methods: Neuropsychological evaluation methods as simple (SRT) and choice reaction-time (CRT) tests, heart rate variability (HRV) measurements, psychological questionnaires. To explore obtained data methods of statistical analysis were used. Results: Obtained data show that different combinations of levels of motivation to achieve success and motivation to avoid failure provoke different psychophysiological states. Conducted experiment revealed that combination of high levels of both motivation to achieve success and motivation to avoid failure provides better psychophysiological state in elite judokas compared to other groups with different combinations of motivational variables. It was shown that motivation to avoid failures had been formed as a personality formation, which compensates excessive tension, caused by high level of motivation to achieve and regulates the psychophysiological state. This phenomenon can be viewed as an effect of training in judokas. Conclusions: Consideration of motivation as a complex multilevel functional system with integrated affective and cognitive processes allows considering this psychic process to regulate activity of a person in actual situation. Obtained data show that different combinations of levels of motivation to achieve success and motivation to avoid failure provoke different psychophysiological states. Conducted experiment revealed that combination of high levels of both motivation to achieve and motivation to avoid provides the high level of the psychophysiological state in elite judokas (psychophysiological state which maintains high level of efficient activity during trainings and competitions). The process of forming of the psychophysiological states in subjects is characterized by the cognitive-regulatory functional system.